Methods of applying hydrogen peroxide to soursop seedlings irrigated with saline water - Veloso, Luana Lucas de Sá Almeida; Capitulino, Jessica Dayanne; Soares de Lima, Geovani; Vieira de Azevedo, Carlos Alberto; Rodrigues da Silva, André Alisson; Gheyi, Hans Raj (Comunicata Scientiae, 2020)
The acclimatization of plants to salt stress, through the application of hydrogen peroxide, occurs due to the activation of the antioxidant defense system. In this sense, the aim of the study was to evaluate the levels of photosynthetic pigments and the photochemical efficiency of soursop seedlings under irrigation with saline water and different methods of applying hydrogen peroxide. The study was carried out in greenhouse conditions, in a 5 x 4 scheme, with five levels of electrical conductivity of irrigation water - CEa (0.6; 1.2; 1.8; 2.4 and 3.0 dS m-1) and four methods of application of hydrogen peroxide-MA (without application of H2O2, application via seed soaking, application via leaf spray and application via seed soaking and leaf spray). The salinity of irrigation water up to 1.4 and 1.1 dS m-1 caused an increase in the synthesis of chlorophyll b and carotenoids, respectively. Irrigation with water from 0.6 dS m-1 reduced the synthesis of chlorophyll a and total of soursop plants. The application of 20 μm of H2O2 via seed imbibition results in an increase in the contents of chlorophyll a and b, total, maximum and variable fluorescence of soursop seedlings. Soaking the seeds with hydrogen peroxide increased the initial fluorescence of chlorophyll in plants irrigated with water 1.2 dS m-1.